IMPLEMENTASI DAN PELATIHAN APLIKASI P.O.S UNTUK OPTIMALISASI PENGELOLAAN USAHA PADA KEDAI KOPI JATI - tri wahyuni; ayla zhafira; rahma yulia sifa (PT. ZIVANA CENDEKIAWAN BANGSA, 2025)
The implementation and training of Point of Sale (P.O.S) application at Kedai Kopi Jati aims to improve operational efficiency as well as transaction and service management. As the number of customers grew, the shop needed a more organised and faster system. For this reason, Kedai Kopi Jati's partners were involved in training on the use of the P.O.S application designed to support the smooth running of business processes. The methods applied include hands-on training with simulation of application usage and performance evaluation after its implementation. The training results show that the P.O.S application speeds up transactions and simplifies service management, while partners are able to operate the system independently. The implementation of this technology has contributed to improving service quality and customer satisfaction. This service emphasises the importance of technology implementation in small businesses to improve operational effectiveness and competitiveness.